Development Of An Anti-Bullying Module Based On School Community Participation For A Safe Environment At MAS Darul Musyawirien In 2026 - Mohammad Husaini; Abdul Kirom (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to develop an anti-bullying module based on school community participation to create a safe and conducive learning environment at Darul Musyawirien Private Islamic Senior High School. This study uses a mixed method approach with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The study involved 42 students as research subjects. Data were collected through observation, interviews, expert validation questionnaires, and pretest and posttest tests, while data analysis was carried out qualitatively and quantitatively using paired sample t-tests. The results showed that the developed module was declared feasible based on expert validation results, with a score of 75 from material experts, 75 from media experts, and 95 from language experts. The effectiveness test showed a significant increase in student understanding, with an average score increasing from 61.96 in the pretest to 82.44 in the posttest. Statistical analysis showed a significant difference before and after using the module (t = −11.64084742; p < 0.05). Thus, the anti-bullying module developed is proven to be valid and effective in supporting bullying prevention efforts and creating a safe school environment.